Readiness of Primary School Teachers On Emergency Curriculum Policies During The Covid-19 Pandemic : A Study Investigating Teacher’ Perception - Uswatun Hasanah; Arita Marini; Mohamad Syarif Sumantri; Ahmad Januar (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
Abstract This study aims to explore the readiness of primary school teachers on emergency curriculum policies during the COVID-19 pandemic. Data collection was carried out through semi-structured surveys and interviews with fifty-five elementary school teachers across Jakarta province. Thematic analysis was used in this study. The results of the analysis found three main themes, namely, material organization, learning strategies, and learning assessments. Based on findings, it illustrates that most teachers have tried to be ready to implement emergency curriculum policies during the pandemic. The emergency curriculum has changed the education system in Indonesia, starting from the learning system, the selection of teaching materials, to the assessment system. The results of this study indicate that the success of implementing the emergency curriculum depend on the involvement of teachers and parents in guiding students. Parents must guide and facilitate children's learning while teachers must be creative and innovative in creating enjoyable learning for students. This research can also be a reference for future researchers to develop a learning model during the pandemic period. Keywords: emergency curriculum, teacher’s perception, COVID-19 Abstrak Studi ini bertujuan untuk mengeksplorasi kesiapan guru sekolah dasar terhadap kebijakan kurikulum darurat selama masa pandemic COVID-19. Pengumpulan data dilakukan melalui survei dan wawancara semi-terstruktur dengan 55 guru sekolah dasar yang tersebar di wilayah provinsi DKI Jakarta. Analisis data menggunakan peta tematik kualitatif. Hasil analisis menemukan tiga tema utama yaitu, organisasi materi, strategi pembelajaran, dan penilaian pembelajaran. Berdasarkan hasil penelitian, menggambarkan sebagian besar guru telah berusaha siap untuk mengimplementasikan kebijakan kurikulum darurat selama pandemic. Hasil penelitian ini juga menunjukan bahwa kesuksesan implementasi kurikulum darurat bergantung pada keterlibatan guru dan orang tua dalam membimbing siswa. Orang tua harus membimbing dan memfasilitasi anak belajar sedangkan guru harus kreatif dan inovatif dalam menciptakan pembelajaran yang menyenangkan bagi siswa. Penelitian ini juga dapat menjadi acuan pada peneliti selanjutnya untuk mengembangkan suatu model pembelajaran selama masa pandemic berlangsung. Kata kunci: kurikulum darurat, persepsi guru, COVID-19